Choroidal detachment after topical prostaglandin analogs: Case report - Kessara Pathanapitoon (2018)
Objective: To report three cases of delayed choroidal detachment after treatment with topical prostaglandin analogs Material and Method: Intervention three case reports. Four eyes of three patients with chronic angle closure glaucoma developed choroidal detachment after using topical prostaglandin analogs Results: Three patients with chronic angle closure glaucoma developed chroidal detachment in one week, three weeks and two years after using travoprost, bimatoprost and latanoprost respectively. All of them resolved after discontinuation of these medications. All of the eyes that developed chroidal detachment were pseudophakic Conclusion: Travoprost, bimatoprost and latanoprost may lead to choroidal detachment and hypotony. Pseudophakic patients may be at high risk of the development of chroidal detachment. Topical prostaglandin analogs should be used cautiously in these patients.